DEVELOPING AN AHP-BASED MODEL FOR EVALUATING MITIGATION PROGRAMS FOR FLOOD DISASTER: CASE STUDY IN JAKARTA, INDONESIA: Pengembangan Model AHP- Based untuk Mengevaluasi Program Mitigasi Bencana Banjir: Studi Kasus di Jakarta, Indonesia - Sari, Dharwati Pratama; Anwar, M Ruslin (Jurusan Teknik Sipil Fakultas Teknik Universitas Mataram, 2021)
Throughout the centuries flood disasters have taken a loss of human lives property damage, and economic impacts all over the world. In Jakarta, Indonesia, various alternatives of strategies after flood disasters have been implemented during the past reconstruction project due the high severe damage losses. Unfortunately the programs just issues, based on the damage and losses assessment after recent disasters happened, it indicated the necessity of better flood disaster management for future life’s people in Indonesia. The research focused on flood disaster mitigation program and used as some implementation program from other countries for comparison to propose an appropriate design of mitigation and planned. The approaches use the Analytic Hierarchy Process (AHP) as a decision analysis tool, in order to develop a Program Evaluation Model (PEM) for flood disaster management in Jakarta. In addition, data will be gathered through direct survey with experts. The PEM’s concept is concerned with the selecting the major factors which influence the management of flood disaster in Jakarta, and use the identified factors to evaluate different flood mitigation program from other countries (Taiwan, Japan, Netherlands, United States, and United Kingdom).